Postoperative Radiotherapy for Patients With Resectable Stage III-N2 Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Lei, Tianyu; Li, Jing; Zhong, Hao; Zhang, Huibo; Jin, Yan; Wu, Jie; Li, Lan; Xu, Bin; Song, Qibin; Hu, Qinyong (Frontiers in Oncology, 2021)
Purpose: For resectable cases of stage IIIA-N2 non-small cell lung cancer (NSCLC), the best treatment after surgery is still uncertain. The effect of postoperative radiotherapy (PORT) is controversial. Thus, we performed this updated meta-analysis to reassess the data of PORT in stage IIIA-N2 NSCLC patients, to figure out whether these patients can benefit from PORT. Methods: We conducted searches of the published literature in EMBASE, PubMed, and the Cochrane Library for relevant randomized control trials (RCTs) comparing PORT group with the non-PORT group in NSCLC patients at stage IIIA-N2. These researches allowed the prior chemotherapy in the treatment. We extracted the data from these articles and used the hazard ratios (HRs) and their 95% confidence intervals (CIs) as summary statistics for overall survival (OS), disease-free survival (DFS), local-regional recurrence-free survival (LRFS). Extracted data were used to estimate the effect of PORT. Result: This meta-analysis displayed no benefit in improving OS associated with the use of PORT (HR=0.87; 95% CI, 0.71 to 1.07; p=0.18) but a significantly difference of effect on DFS (HR=0.83; 95% CI, 0.71 to 0.97; p=0.02) and LRFS (HR=0.64; 95% CI, 0.50 to 0.81; p=0.0003) associated with the use of PORT. Subgroup analysis of the use of chemotherapy has no significance. Conclusion: Our findings illustrated that in the postoperative treatment for patients with stage IIIA-N2 NSCLC, PORT contributes to a significantly increased DFS and LRFS and may not associate with an improved OS. Therefore, currently, radiotherapy to the mediastinum after surgery cannot be the standard of care to be recommended for all patients with stage IIIA NSCLC with mediastinal nodal involvement.